Hardware Implementation of a Stream Cipher Based on a Chaotic Map - Torre Bordes, Diego; García, Miguel; Sánchez-Azqueta, Carlos; Aldea, Concepción (Jornada de Jóvenes Investigadores del I3A, 2018)
This work focuses in a synthesis and subsequent verification of a stream cipher based on the Skew Tent Map. The paper concludes with the analysis of possible modifications in order to improve the quality of the generated random sequences.